Actocardiogram : analysis of fetal motion and heart rate - Maeda, Kazuo (India : Jaypee Brothers Medical Publisers, 2016)
Actocardiogram (ACG) records fetal heart rate, direct fetal movements and uterine contractions using simple probes attached on the pregnant abdomen, and recorded on a moving chart. The same diagnosis is achieved as common cardiotocography (CTG), while fetal heart rate increases parallel to fetal movement, and unsolved problems in the CTG was solved by ACG, e.g. benign physiologic sinusoidal heart rate is diagnosed by cyclically changing fetal movements. Fetal hypoxia progresses according to changing ACG till severe fetal brain damage in the loss of fetal heart rate (FHR) variability. Fetal short-and long-term outcomes are diagnosed using the ratio of fetal heart rate acceleration duration to the fetal movement bursts duration. Fetal behaviour is decided using ACG parameter values. The "Actocardiogram" book details these advantages.
Electronic Fetal Monitoring and Cardiotocogram 1 2. Actocardiogram 3. Fetal Response to Acoustic and Visual Stimulation 4. Prediction, Evaluation and Management of Hypoxia in Fetal Growth Restriction 2 5. Actocardiographic Studies on Fetal Central Nervous System Lesions 6. Short- and Long-term Fetal Outcomes of Fetal Disorders Determined by the A/B Ratio of Actocardiogram 7. Developments of Fetal Heart Rate Acceleration 8. Automatic Computerized Analysis and Diagnosis of Fetal Heart Rate: The Expert System on Fetal Heart Rate 9. Artificial Neural Network Computer Diagnosis of Fetal Heart Rate 10. Computerized Actocardiogram for the Diagnosis of Fetal Behavior 11. Computer Diagnosis of Sinusoidal FHR and the Loss of Variability with Frequency Spectrum Analysis 12. Centralized Automatic Diagnosis of Fetal Heart Rate with Rapid and Direct Alarm System 13. Controversies of CTG Solved by Actocardiogram 14. Strategies to Prevent Fetal Brain Damages
Incluye contenido
Incluye indice
Keywords: HEART; ANALYSIS FETAL